2018
DOI: 10.1093/biolre/ioy196
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor isoforms and effects of glucocorticoids in ovulated mouse oocytes and preimplantation embryos†

Abstract: To investigate possible involvement of glucocorticoid receptor (GR) in mediating effects of maternal stress or therapeutically administered glucocorticoids on early embryo we analyzed the expression of GR subtypes in ovulated mouse oocytes and preimplantation embryos. RT-PCR analysis results showed that GRα and GRγ transcripts are relatively highly expressed in mouse oocytes, and both transcripts are present at lower amounts in preimplantation embryos. We also detected low expression of two other splice varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…The impact of glucocorticoids on their target organs is primarily modulated by the local number of glucocorticoid receptors (GRs) and the concentration of active hormone available to bind to the GRs ( Table 1 ) [ 22 , 48 , 49 ]. NR3C1 is one of the main GR subtypes that has been shown to be expressed in the ovaries of many different mammalian species [ 17 , 20 , 21 , 22 , 50 , 51 , 52 ] and is part of the nuclear receptor subfamily ligand-dependent transcription factors [ 50 ]. NR3C1 forms a receptor complex upon binding to cortisol, which translocates from the cytoplasm to the nucleus and binds to glucocorticoid response elements (GREs) on DNA to alter transcription and downstream gene expression ( Figure 1 ) [ 17 , 50 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The impact of glucocorticoids on their target organs is primarily modulated by the local number of glucocorticoid receptors (GRs) and the concentration of active hormone available to bind to the GRs ( Table 1 ) [ 22 , 48 , 49 ]. NR3C1 is one of the main GR subtypes that has been shown to be expressed in the ovaries of many different mammalian species [ 17 , 20 , 21 , 22 , 50 , 51 , 52 ] and is part of the nuclear receptor subfamily ligand-dependent transcription factors [ 50 ]. NR3C1 forms a receptor complex upon binding to cortisol, which translocates from the cytoplasm to the nucleus and binds to glucocorticoid response elements (GREs) on DNA to alter transcription and downstream gene expression ( Figure 1 ) [ 17 , 50 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…NR3C1 is one of the main GR subtypes that has been shown to be expressed in the ovaries of many different mammalian species [ 17 , 20 , 21 , 22 , 50 , 51 , 52 ] and is part of the nuclear receptor subfamily ligand-dependent transcription factors [ 50 ]. NR3C1 forms a receptor complex upon binding to cortisol, which translocates from the cytoplasm to the nucleus and binds to glucocorticoid response elements (GREs) on DNA to alter transcription and downstream gene expression ( Figure 1 ) [ 17 , 50 , 52 , 53 ]. Two main enzymes, 11b-hydroxysteroid dehydrogenase type 1 (HSD11B1) and type 2 (HSD11B2), are responsible for controlling the concentration of active glucocorticoids within target organs [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical study showed that both increased stress levels and serum levels of cortisol (CORT) are associated with missed abortion (Tian & Kang, 2014). Corticosterone treatment during in vitro culture inhibits early embryo development from the two‐cell stage to blastocysts in mice (Čikoš et al, 2019). Administration of dexamethasone (a synthetic glucocorticoid) during gestation results in increased follicular atresia and reduction of the pool of healthy primordial follicles in the ovary of neonatal spiny mice (Hulas‐Stasiak et al, 2016).…”
Section: Introductionmentioning
confidence: 99%